A method for producing a zirconium alloy ingot having a low chlorine content
Patent Information
- Application Number
- CN202410305811.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-18
AI Technical Summary
氯元素来源于锆合金制备的原材料海绵锆,目前海绵锆制备均由单质镁还原四氯化锆而来,虽然海绵锆经过蒸馏能除掉绝大部分氯元素,但仍有少量氯元素以氯化物的形式残留在海绵锆内部无法彻底去除,一般占海绵锆的质量百分数0.002%~0.1%,氯含量较高的一般为0.05%~0.1%,其中,氯元素含量越低的海绵锆成本越高
[0032]1.本发明一种低氯元素含量锆合金铸锭的制备方法,该制备方法通过对原材料进行筛选及检测,然后通过熔炼工艺、以及对熔炼得到的铸锭表面进行氯化物去除,再对氯化物去除后的铸锭进行熔炼,保证制备出的锆合金铸锭氯元素含量小于0.0001%,并经过超声探伤检测到整支锆合金铸锭无缺陷,同时其他合金元素也均满足技术条件要求,制备出的产品质量稳定性高,经济性较好。
Smart Images

Figure CN118385480B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of zirconium alloy ingot preparation technology, specifically relating to a method for preparing zirconium alloy ingots with low chlorine content. Background Technology
[0002] Zirconium alloys are key structural materials for nuclear reactor cores. Various grades of zirconium alloys have been developed both domestically and internationally, such as Zr-2 alloy, Zr-4 alloy, M5 alloy, HANA6 alloy, Zirlo alloy, and new zirconium alloys. All zirconium alloys require a chlorine content ≤0.0020%, especially for special zirconium alloy tubing used in Candu reactors, which requires a chlorine content ≤0.0001%, placing even higher demands on chlorine control. Chlorine originates from sponge zirconium, the raw material for zirconium alloy production. Currently, sponge zirconium is produced by reducing zirconium tetrachloride with elemental magnesium. Although distillation removes most of the chlorine from sponge zirconium, a small amount remains as chlorides within the sponge zirconium and cannot be completely removed. This typically accounts for 0.002%–0.1% of the mass of sponge zirconium, with higher chlorine contents generally ranging from 0.05% to 0.1%. Lower chlorine content generally results in higher costs for sponge zirconium.
[0003] Chlorides in sponge zirconium are mostly volatile substances. Even after vacuum melting, some zirconium alloy ingots made from sponge zirconium with high chloride content still fail to meet technical requirements for chloride content. Furthermore, ingots prepared from sponge zirconium with high chloride content after no more than two melting processes exhibit localized defects during ultrasonic testing, severely impacting the quality of subsequent products. Since the characteristics of chlorides in sponge zirconium can only be controlled through the ingot melting process, the challenge lies in how to use sponge zirconium with high chloride content to produce zirconium alloy ingots with low chloride content, thereby reducing production costs.
[0004] In view of this, the inventors provide a method for preparing zirconium alloy ingots with low chlorine content to solve the above-mentioned technical problems. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and propose a method for preparing zirconium alloy ingots with low chlorine content. This method uses sponge zirconium as the main raw material, and involves screening sponge zirconium particles, adjusting the process parameters of each vacuum consumable arc melting process, and performing shot blasting, turning and cleaning on the surface of the ingot that does not show metallic color after cleaning. The treated ingot is then melted to finally obtain a qualified zirconium alloy ingot with extremely low chlorine content.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A method for preparing a zirconium alloy ingot with low chlorine content involves first mixing screened and tested sponge zirconium with alloying elements, then pressing and welding it to obtain a consumable electrode, and then performing the following two-stage melting process on the consumable electrode.
[0008] During the first stage of smelting, the consumable electrode is placed in the smelting equipment and heating is started. After heating for a set time, unidirectional stirring is started, and intermittent stirring is used to allow the chloride in the consumable electrode to fully volatilize and distribute on the surface of the smelted ingot. After the consumable electrode has melted completely, heating is stopped and cooling is carried out under an inert gas atmosphere. After cooling is completed, the ingot is taken out.
[0009] The surface of the ingot is cleaned. If the metal color is exposed, the second melting stage is started. Otherwise, the surface of the ingot is shot-blasted, turned and cleaned in sequence to remove chlorides, and then the first stage of melting is carried out.
[0010] In the second stage of smelting, the ingot with exposed metallic color is first placed into the smelting equipment and heated. After heating for a set time, bidirectional stirring is started, and intermittent stirring is used to ensure that the alloying elements other than chlorine are evenly distributed in the smelted ingot and that chlorides are fully volatilized. After the ingot with exposed metallic color has melted completely, heating is stopped and it is cooled under an inert gas atmosphere. After cooling is completed, a zirconium alloy ingot with a chlorine content of <0.0001% is obtained.
[0011] The number of times the first and second stages of smelting are performed in this invention is not limited.
[0012] Furthermore, the screened sponge zirconium comprises elements with a Cl content of 0.05% to 0.1%.
[0013] Sponge zirconium with a particle size ≥ 2 mm.
[0014] Furthermore, the tested sponge zirconium includes 100% visual inspection, and sponge zirconium with abnormal surface color and no pores is rejected.
[0015] Furthermore, the pressing and welding process to obtain the consumable electrode includes:
[0016] After screening and testing, the sponge zirconium was divided into two parts. One part of the sponge zirconium was added into the press mold cavity. Then, all the alloying elements were evenly sprinkled on the sponge zirconium in the mold cavity. The other part of the sponge zirconium was added into the press mold cavity. Finally, the press was started to press the sponge zirconium to obtain the electrode block.
[0017] The electrode block is welded in a vacuum plasma welding box, and after cooling for a set time after welding, a consumable electrode is obtained.
[0018] Furthermore, when welding in a vacuum plasma welding box, the welding current is set to 400A to 500A; the cooling time is set to 60min to 90min.
[0019] It should be noted that zirconium alloy ingots typically contain alloying elements such as tin, chlorine, niobium, and chromium, each with different physical properties. For example, chromium is highly volatile, but reducing chlorine levels requires creating a smelting environment conducive to volatilization. A challenge lies in controlling chlorine levels without affecting the distribution of other alloying elements in the zirconium alloy ingot. Therefore, this invention employs precise melting rate control and stirring technology during smelting to ensure that chlorine is largely volatilized and removed from the zirconium while maintaining a uniform distribution of other alloying elements. The smelting process is as follows:
[0020] Furthermore, the first stage of melting includes the following specific process when the consumable electrode is melted twice in a vacuum consumable arc furnace:
[0021] Before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ440mm~Φ460mm is selected, and the melting speed corresponding to the crystallizer is 10kg / min~16kg / min;
[0022] The consumable electrode is first melted, with a melting current of 11000A to 14000A, a melting voltage of 32V to 36V, and a melting stirring magnetic field strength of 23Gs to 27Gs, and unidirectional stirring is used; after the first melting is completed, it is cooled in an inert gas state to obtain a first ingot, and the cooling time is ≥6h.
[0023] Before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ540mm~Φ560mm is selected, and the melting speed corresponding to the crystallizer is 18kg / min~22kg / min;
[0024] The primary ingot is subjected to secondary melting. During the secondary melting process, the melting current is 17000A~21000A, the melting voltage is 34V~38V, the melting stirring magnetic field strength is 10Gs~16Gs, and unidirectional stirring is adopted. After the secondary melting is completed, it is cooled under an inert gas state to obtain a secondary ingot. The cooling time is ≥7h.
[0025] It should be noted that during the first smelting, the chlorides are instantly heated by the electric arc, generating a large amount of gas. This gas splashes some of the molten metal onto the inner wall of the crystallizer, where it cools and solidifies rapidly. This results in a metal shell forming on the outer surface of the primary ingot. This metal shell encapsulates the chlorides that have drained from the molten metal onto the ingot surface. To remove the chlorides from the surface of the primary ingot as much as possible, this metal shell needs to be removed before cleaning. Therefore, shot blasting is first used to clean the surface of the primary ingot to prevent fire during subsequent lathe processing. Then, the surface metal shell is removed using a lathe. Finally, a primary ingot cleaning is performed to thoroughly remove the surface chlorides. The same principle applies to smelting processes that occur twice or more.
[0026] Furthermore, the second stage of smelting includes: smelting the cleaned ingots, which have exposed their metallic color, in a vacuum arc furnace, setting the vacuum degree in the vacuum arc furnace to ≤0.5Pa and the pressure rise rate to ≤0.3Pa / min before smelting; selecting a crystallizer with a diameter of Φ640mm~Φ660mm, and the smelting speed corresponding to the crystallizer to be 26kg / min~30kg / min;
[0027] During the smelting process, the smelting current is 22000A~27000A, the smelting voltage is 36V~40V, the smelting stirring magnetic field strength is 4Gs~8Gs, and bidirectional stirring is adopted; after the smelting is completed, it is cooled under an inert gas state to obtain a zirconium alloy ingot with a Cl element content of <0.0001%, and the cooling time is ≥8h.
[0028] Furthermore, the bidirectional stirring is set to change the stirring direction every 10 to 20 seconds.
[0029] Furthermore, each crystallizer is equipped with a cooling channel, the inlet water temperature of which does not exceed 38°C and the outlet water temperature of which does not exceed 45°C.
[0030] Furthermore, the heating time is 8 to 10 minutes, and the intermittent stirring includes unidirectional / bidirectional stirring for 80 to 90 seconds, followed by a 20 to 30 second pause, and then the cycle repeats; the inert gas is argon.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. This invention discloses a method for preparing a zirconium alloy ingot with low chloride content. The method involves screening and testing raw materials, followed by a smelting process and chloride removal from the surface of the smelted ingot. The chloride-removed ingot is then smelted again to ensure that the chloride content of the prepared zirconium alloy ingot is less than 0.0001%. Ultrasonic testing confirms that the entire zirconium alloy ingot is defect-free, and other alloying elements also meet the technical requirements. The resulting product has high quality stability and good economic efficiency.
[0033] 2. The present invention provides a method for preparing a zirconium alloy ingot with low chloride content. The sponge zirconium used in this preparation method has a chloride content of 0.05% to 0.1%, and the zirconium alloy ingot prepared by the method of the present invention has a chloride content of <0.0001%. Therefore, the present invention can solve the problem of preparing a zirconium alloy ingot with low chloride content using sponge zirconium with high chloride content.
[0034] 3. This invention discloses a method for preparing a low-chlorine-content zirconium alloy ingot. In the first stage of melting, specific melting parameters are set to increase the melting speed and reduce the stirring magnetic field strength, causing the molten pool to rotate unidirectionally. This weakens the cooling intensity during melting, resulting in a flattened molten pool distribution, promoting the full volatilization of chlorides and their distribution on the ingot surface. This facilitates the removal of volatilized chlorides through shot blasting, turning, and cleaning, thereby better removing chlorine from the sponge zirconium. The first-stage melting and surface treatment processes significantly reduce chlorine levels. Therefore, in the second stage of melting, the melting parameters and stirring method are designed primarily to adjust the alloy elements in the ingot while also considering chlorine removal. The resulting zirconium alloy ingot has a qualified composition and extremely low chlorine content. The zirconium alloy ingot prepared by this invention exhibits excellent performance, fully meeting the requirements of subsequent finished products. It features low investment, ease of operation, broad application prospects, and ease of industrial production.
[0035] 4. The present invention provides a method for preparing a zirconium alloy ingot with low chloride content. The surface treatment is designed to first perform shot blasting, followed by turning and cleaning. Shot blasting can effectively remove volatiles from the surface of the ingot. Most of these volatiles are chlorides from sponge zirconium, which are highly flammable. Therefore, shot blasting first avoids the risk of zirconium chips igniting and causing safety accidents during subsequent lathe machining. Attached Figure Description
[0036] The accompanying drawings are incorporated in and form part of this specification, and together with the description serve to explain the principles of the invention.
[0037] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0038] Figure 1 This is a schematic diagram of sampling during ingot testing in various embodiments and comparative embodiments of the present invention. Detailed Implementation
[0039] Exemplary embodiments will now be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples of apparatuses consistent with some aspects of the invention as detailed in the appended claims.
[0040] Example 1
[0041] This invention provides a method for preparing a zirconium alloy ingot with low chlorine content, specifically including the following steps:
[0042] Step 1: Select nuclear-grade sponge zirconium with a Cl element content of 0.05%, and screen it to remove particles with a particle size smaller than Φ2mm. Visually inspect the sponge zirconium with abnormal black or gray color and sponge zirconium without pores, and prepare the alloying elements Sn, Fe, and Cr.
[0043] Step 2: Using a pressing force of 4500t, the weighed nuclear-grade sponge zirconium is pressed into electrode blocks weighing 150kg / block, with the specifications of the electrode blocks being Φ360mm×300mm.
[0044] Specifically, the screened and tested sponge zirconium is divided into two equal parts by weight. One part of sponge zirconium is first added into the mold cavity of the press. Then, all the alloying elements Sn, Fe and Cr are evenly sprinkled on the sponge zirconium in the mold cavity. The other part of sponge zirconium is then added into the mold cavity of the press. Finally, the press is started to press the sponge zirconium, and a total of 20 electrode blocks are obtained.
[0045] Specifically, a 50MN press should be selected;
[0046] Step 3: Divide the 20 electrode blocks into two groups of 10 each and weld them into consumable electrodes in a vacuum plasma welding box to obtain 2 consumable electrodes; specifically, the welding current is 460A and the cooling time after welding is 1 hour.
[0047] Step 4, primary melting: The two consumable electrodes obtained in Step 3 are melted in a 3t vacuum consumable arc furnace to obtain two primary ingots. The specifications of the primary ingots after melting are Φ435mm×1550mm.
[0048] Specifically, before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ440mm is selected; melting begins, with the melting current set to 11000A, the melting voltage set to 32V, the melting stirring magnetic field strength set to 23Gs, and the melting speed set to 10kg / min. After heating for 9 minutes, the temperature of the vacuum self-consuming electric arc furnace rises, and unidirectional stirring begins until the self-consuming electrode is completely melted. Then, stirring and heating are stopped, and the furnace is cooled for 6 hours under argon atmosphere.
[0049] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The unidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating.
[0050] Step 5: After cooling and exiting the furnace, the two primary ingots are cleaned separately on an ingot cleaning machine. After cleaning, the surfaces of the two primary ingots are black and no metallic color is exposed. Further, the surfaces of the two primary ingots are treated separately. Specifically, the two primary ingots are first shot blasted on a roller conveyor shot blasting machine to remove the black volatiles on the surface. Then, the surface spatter shell is removed on a lathe. Finally, the volatiles are cleaned off on the ingot cleaning machine to expose the metallic color of the primary ingots.
[0051] Step 6, Secondary Melting: The two primary ingots obtained in Step 5 are smelted in a 3t vacuum self-consuming electric arc furnace to obtain one secondary ingot. The secondary ingot after smelting has a size of Φ535mm×2050mm.
[0052] Specifically, before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ540mm is selected; melting begins, with the melting current set to 17000A, the melting voltage set to 34V, the melting stirring magnetic field strength set to 10Gs, and the melting speed set to 18kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and unidirectional stirring begins until the ingot is completely melted. Then, stirring and heating are stopped, and the furnace is cooled for 7 hours under argon atmosphere.
[0053] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 40°C. The unidirectional stirring operation adopts a method of stirring for 85 seconds, pausing for 25 seconds, and then recirculating.
[0054] Step 7: Clean the secondary ingots after cooling and exiting the furnace on an ingot cleaning machine. After cleaning, the surface of the secondary ingots will show a metallic color, and then it will enter the second stage of smelting.
[0055] Step 8, Third Melting: The secondary ingot obtained in Step 7 is melted three times in a 3t vacuum self-consuming electric arc furnace. The specifications of the third ingot after melting are Φ635mm×1520mm.
[0056] Specifically, before the three melting processes, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ640mm is selected; melting begins, with the melting current set to 22000A, melting voltage set to 36V, melting stirring magnetic field strength set to 4Gs, and melting speed set to 26kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and bidirectional stirring begins until the secondary ingot is melted. Stirring is then stopped, heating is stopped, and the furnace is cooled under argon atmosphere for 8 hours to obtain the zirconium alloy ingot.
[0057] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 39°C. The bidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating, and the stirring direction is changed every 10 seconds.
[0058] To further illustrate the effectiveness of the present invention, this embodiment samples and analyzes the chemical composition of the obtained zirconium alloy ingot, and uses a handheld UT flaw detector to conduct ultrasonic flaw detection on the outer circle. The test results show that the zirconium alloy ingot has qualified composition and no defects.
[0059] Example 2
[0060] This invention provides a method for preparing a zirconium alloy ingot with low chlorine content, specifically including the following steps:
[0061] Step 1: Select nuclear-grade sponge zirconium with a Cl content of 0.08%, and screen it to remove particles with a particle size smaller than Φ2mm. Visually inspect the sponge zirconium with abnormal black or gray color and sponge zirconium without pores, and prepare the alloying element Nb.
[0062] Step 2: Using a pressing force of 4500t, the weighed nuclear-grade sponge zirconium is pressed into electrode blocks weighing 150kg / block, with the specifications of the electrode blocks being Φ360mm×300mm.
[0063] Specifically, the selected and tested sponge zirconium was divided into two equal parts by weight. One part of the sponge zirconium was first added into the mold cavity of the press. Then, all the alloying element Nb was evenly sprinkled on the sponge zirconium in the mold cavity. The other part of the sponge zirconium was then added into the mold cavity of the press. Finally, the press was started to press the sponge zirconium, and a total of 20 electrode blocks were obtained.
[0064] Specifically, a 50MN press should be selected;
[0065] Step 3: Divide the 20 electrode blocks into two groups of 10 each and weld them into consumable electrodes in a vacuum plasma welding box to obtain 2 consumable electrodes; specifically, the welding current is 440A and the cooling time after welding is 80min.
[0066] Step 4, primary melting: The two consumable electrodes obtained in Step 3 are melted in a 3t vacuum consumable arc furnace to obtain two primary ingots. The specifications of the primary ingots after melting are Φ445mm×1500mm.
[0067] Specifically, before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ450mm is selected; melting begins, with the melting current set to 12500A, the melting voltage set to 34V, the melting stirring magnetic field strength set to 25Gs, and the melting speed set to 13kg / min. After heating for 10 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and unidirectional stirring begins until the self-consuming electrode is completely melted. Then, stirring and heating are stopped, and the furnace is cooled for 7 hours under argon atmosphere.
[0068] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The unidirectional stirring operation adopts a method of stirring for 90 seconds, pausing for 25 seconds, and then recirculating.
[0069] Step 5: After cooling and exiting the furnace, the two primary ingots are cleaned separately on an ingot cleaning machine. After cleaning, the surfaces of the two primary ingots are black and no metallic color is exposed. Further, the surfaces of the two primary ingots are treated separately. Specifically, the two primary ingots are first shot blasted on a roller conveyor shot blasting machine to remove the black volatiles on the surface. Then, the surface spatter shell is removed on a lathe. Finally, the volatiles are cleaned off on the ingot cleaning machine to expose the metallic color of the primary ingots.
[0070] Step 6, Secondary Melting: The two primary ingots obtained in Step 5 are smelted in a 3t vacuum self-consuming electric arc furnace to obtain one secondary ingot. The secondary ingot after smelting has a size of Φ545mm×2000mm.
[0071] Specifically, before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ550mm is selected; melting begins, with the melting current set to 19000A, the melting voltage set to 36V, the melting stirring magnetic field strength set to 13Gs, and the melting speed set to 20kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and unidirectional stirring begins until the ingot is completely melted. Then, stirring and heating are stopped, and the furnace is cooled under argon atmosphere for 8 hours.
[0072] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 40°C. The unidirectional stirring operation adopts a method of stirring for 90 seconds, pausing for 30 seconds, and then recirculating.
[0073] Step 7: Clean the secondary ingots after cooling and exiting the furnace on an ingot cleaning machine. After cleaning, the surface of the secondary ingots will show a metallic color, and then it will enter the second stage of smelting.
[0074] Step 8, Third Melting: The secondary ingot obtained in Step 7 is melted three times in a 3t vacuum self-consuming electric arc furnace. The specifications of the third ingot after melting are Φ645mm×1500mm.
[0075] Specifically, before the three melting processes, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ650mm is selected; melting begins, with the melting current set to 24000A, melting voltage set to 38V, melting stirring magnetic field strength set to 6Gs, and melting speed set to 30kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and bidirectional stirring begins until the secondary ingot is melted. Stirring is then stopped, heating is stopped, and the furnace is cooled under argon atmosphere for 9 hours to obtain the zirconium alloy ingot.
[0076] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 39°C. The bidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating, and the stirring direction is changed every 15 seconds.
[0077] To further illustrate the effectiveness of the present invention, this embodiment samples and analyzes the chemical composition of the obtained zirconium alloy ingot, and uses a handheld UT flaw detector to conduct ultrasonic flaw detection on the outer circle. The test results show that the zirconium alloy ingot has qualified composition and no defects.
[0078] Example 3
[0079] This invention provides a method for preparing a zirconium alloy ingot with low chlorine content, specifically including the following steps:
[0080] Step 1: Select nuclear-grade sponge zirconium with a Cl content of 0.1% and screen it to remove particles with a diameter of less than Φ2mm. Visually inspect the sponge zirconium with abnormal black or gray color and sponge zirconium without pores, and prepare alloying elements Nb, Sn, Fe and Cr.
[0081] Step 2: Using a pressing force of 4500t, the weighed nuclear-grade sponge zirconium is pressed into electrode blocks weighing 150kg / block, with the specifications of the electrode blocks being Φ360mm×300mm.
[0082] Specifically, the screened and tested sponge zirconium was divided into two equal parts by weight. One part of the sponge zirconium was first added into the press mold cavity. Then, all the alloying elements Nb, Sn, Fe and Cr were evenly sprinkled on the sponge zirconium in the mold cavity. The other part of the sponge zirconium was then added into the press mold cavity. Finally, the press was started to press the zirconium, and a total of 20 electrode blocks were obtained.
[0083] Specifically, a 50MN press should be selected;
[0084] Step 3: Divide the 20 electrode blocks into two groups of 10 each and weld them into consumable electrodes in a vacuum plasma welding box to obtain 2 consumable electrodes; specifically, the welding current is 500A and the cooling time after welding is 90min.
[0085] Step 4, primary melting: The two consumable electrodes obtained in Step 3 are melted in a 3t vacuum consumable arc furnace to obtain two primary ingots. The specifications of the primary ingots after melting are Φ455mm×1490mm.
[0086] Specifically, before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ460mm is selected; melting begins, with the melting current set to 14000A, the melting voltage set to 36V, the melting stirring magnetic field strength set to 27Gs, and the melting speed set to 16kg / min. After heating for 10 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and unidirectional stirring begins until the self-consuming electrode is completely melted. Then, stirring and heating are stopped, and the furnace is cooled under argon atmosphere for 8 hours.
[0087] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The unidirectional stirring operation adopts a method of stirring for 90 seconds, pausing for 28 seconds, and then recirculating.
[0088] Step 5: After cooling and exiting the furnace, the two primary ingots are cleaned separately on an ingot cleaning machine. After cleaning, the surfaces of the two primary ingots are black and no metallic color is exposed. Further, the surfaces of the two primary ingots are treated separately. Specifically, the two primary ingots are first shot blasted on a roller conveyor shot blasting machine to remove the black volatiles on the surface. Then, the surface spatter shell is removed on a lathe. Finally, the volatiles are cleaned off on the ingot cleaning machine to expose the metallic color of the primary ingots.
[0089] Step 6, Secondary Melting: The two primary ingots obtained in Step 5 are smelted in a 3t vacuum self-consuming electric arc furnace to obtain one secondary ingot. The secondary ingot after smelting has a size of Φ555mm×1900mm.
[0090] Specifically, before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ560mm is selected; melting begins, with the melting current set to 21000A, the melting voltage set to 38V, the melting stirring magnetic field strength set to 16Gs, and the melting speed set to 22kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and unidirectional stirring begins until the ingot is melted in one stage. Then, stirring and heating are stopped, and the furnace is cooled under argon atmosphere for 9 hours.
[0091] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 40°C. The unidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 30 seconds, and then recirculating.
[0092] Step 7: Clean the secondary ingots after cooling and exiting the furnace on an ingot cleaning machine. After cleaning, the surface of the secondary ingots will show a metallic color, and then it will enter the second stage of smelting.
[0093] Step 8, Third Melting: The secondary ingot obtained in Step 7 is melted three times in a 3t vacuum self-consuming electric arc furnace. The specifications of the third ingot after melting are Φ655mm×1450mm.
[0094] Specifically, before the three melting processes, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ660mm is selected; melting begins, with the melting current set to 27000A, melting voltage set to 40V, melting stirring magnetic field strength set to 8Gs, and melting speed set to 28kg / min. After heating for 9 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and bidirectional stirring begins until the secondary ingot is melted. Stirring is then stopped, heating is stopped, and the furnace is cooled for 10 hours under argon atmosphere to obtain the zirconium alloy ingot.
[0095] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 39°C. The bidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating, and the stirring direction is changed every 20 seconds.
[0096] To further illustrate the effectiveness of the present invention, this embodiment samples and analyzes the chemical composition of the obtained zirconium alloy ingot, and uses a handheld UT flaw detector to conduct ultrasonic flaw detection on the outer circle. The test results show that the zirconium alloy ingot has qualified composition and no defects.
[0097] Example 4
[0098] This invention provides a method for preparing a zirconium alloy ingot with low chlorine content, specifically including the following steps:
[0099] Step 1: Select nuclear-grade sponge zirconium with a Cl content of 0.1% and screen it to remove particles with a diameter of less than Φ2mm. Visually inspect the sponge zirconium with abnormal black or gray color and sponge zirconium without pores, and prepare the alloying elements Sn, Fe, Cr and Ni.
[0100] Step 2: Using a pressing force of 4500t, the weighed nuclear-grade sponge zirconium is pressed into electrode blocks weighing 150kg / block, with the specifications of the electrode blocks being Φ360mm×300mm.
[0101] Specifically, the screened and tested sponge zirconium is divided into two equal parts by weight. One part of sponge zirconium is first added into the mold cavity of the press. Then, all the alloying elements Sn, Fe, Cr and Ni are evenly sprinkled on the sponge zirconium in the mold cavity. The other part of sponge zirconium is then added into the mold cavity of the press. Finally, the press is started to press the sponge zirconium, and a total of 20 electrode blocks are obtained.
[0102] Specifically, a 50MN press should be selected;
[0103] Step 3: Divide the 20 electrode blocks into two groups of 10 each and weld them into consumable electrodes in a vacuum plasma welding box to obtain 2 consumable electrodes; specifically, the welding current is 500A and the cooling time after welding is 90min.
[0104] Step 4, primary melting: The two consumable electrodes obtained in Step 3 are melted in a 3t vacuum consumable arc furnace to obtain two primary ingots. The specifications of the primary ingots after melting are Φ455mm×1490mm.
[0105] Specifically, before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ460mm is selected; melting begins, with the melting current set to 14000A, the melting voltage set to 36V, the melting stirring magnetic field strength set to 27Gs, and the melting speed set to 16kg / min. After heating for 10 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and unidirectional stirring begins until the self-consuming electrode is completely melted. Then, stirring and heating are stopped, and the furnace is cooled under argon atmosphere for 8 hours.
[0106] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The unidirectional stirring operation adopts a method of stirring for 90 seconds, pausing for 30 seconds, and then recirculating.
[0107] Step 5: After cooling and exiting the furnace, the two primary ingots are cleaned separately on an ingot cleaning machine. After cleaning, the surfaces of the two primary ingots are black and no metallic color is exposed. Further, the surfaces of the two primary ingots are treated separately. Specifically, the two primary ingots are first shot blasted on a roller conveyor shot blasting machine to remove the black volatiles on the surface. Then, the surface spatter shell is removed on a lathe. Finally, the volatiles are cleaned off on the ingot cleaning machine to expose the metallic color of the primary ingots.
[0108] Step 6, Secondary Melting: The two primary ingots obtained in Step 5 are smelted in a 3t vacuum self-consuming electric arc furnace to obtain one secondary ingot. The secondary ingot after smelting has a size of Φ555mm×1900mm.
[0109] Specifically, before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ560mm is selected; melting begins, with the melting current set to 21000A, the melting voltage set to 38V, the melting stirring magnetic field strength set to 16Gs, and the melting speed set to 22kg / min. After heating for 9 minutes, the temperature of the vacuum self-consuming electric arc furnace rises, and unidirectional stirring begins until the first ingot is melted. Then, stirring and heating are stopped, and the furnace is cooled for 9 hours under argon atmosphere.
[0110] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 40°C. The unidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating.
[0111] Step 7: Clean the secondary ingots after cooling and exiting the furnace on an ingot cleaning machine. After cleaning, the surface of the secondary ingots will show a metallic color, and then it will enter the second stage of smelting.
[0112] Step 8, Third Melting: The secondary ingot obtained in Step 7 is melted three times in a 3t vacuum self-consuming electric arc furnace. The specifications of the third ingot after melting are Φ655mm×1450mm.
[0113] Specifically, before the three-stage melting process, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate to ≤0.3Pa / min; a crystallizer with a diameter of Φ660mm is selected; melting begins, with the melting current set to 27000A, melting voltage to 40V, melting stirring magnetic field strength to 8Gs, and melting speed to 28kg / min. After heating for 9 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and bidirectional stirring begins until the secondary ingot is completely melted. Stirring is then stopped, heating is stopped, and the furnace is cooled for 10 hours under argon atmosphere to obtain the tertiary ingot.
[0114] Step 9, Four-time melting: The three-time ingots obtained in Step 8 are melted four times in a 3t vacuum self-consuming electric arc furnace. The specifications of the three-time ingots after melting are Φ655mm×1450mm.
[0115] Specifically, before the four melting processes, the vacuum degree in the vacuum arc furnace is set to ≤0.5Pa and the pressure rise rate to ≤0.3Pa / min; a crystallizer with a diameter of Φ660mm is selected; melting begins with a melting current of 27000A, a melting voltage of 40V, a melting stirring magnetic field strength of 8Gs, and a melting speed of 28kg / min. After heating for 9 minutes, the temperature of the vacuum arc furnace increases, and bidirectional stirring begins until the secondary ingot is melted. Stirring is then stopped, heating is stopped, and the furnace is cooled for 10 hours under argon atmosphere to obtain the zirconium alloy ingot.
[0116] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 39°C. The bidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating, and the stirring direction is changed every 15 seconds.
[0117] To further illustrate the effectiveness of the present invention, this embodiment samples and analyzes the chemical composition of the obtained zirconium alloy ingot, and uses a handheld UT flaw detector to conduct ultrasonic flaw detection on the outer circle. The test results show that the zirconium alloy ingot has qualified composition and no defects.
[0118] Comparative Example 1
[0119] This embodiment includes the following steps:
[0120] Step 1: Select nuclear-grade sponge zirconium with a Cl content of 0.05%, and prepare alloying elements Sn, Fe, and Cr;
[0121] Step 2: Using a pressing force of 4500t, the weighed nuclear-grade sponge zirconium is pressed into electrode blocks weighing 150kg / block, with the electrode blocks having a size of Φ360mm×300mm.
[0122] Specifically, the screened and tested sponge zirconium was divided into two equal parts by weight. One part of the sponge zirconium was first added into the mold cavity of the press. Then, all the alloying elements Sn, Fe and Cr were evenly sprinkled on the sponge zirconium in the mold cavity. The other part of the sponge zirconium was then added into the mold cavity of the press. Finally, the press was started to press the sponge zirconium, and a total of 20 electrode blocks were obtained.
[0123] Specifically, a 50MN press should be selected;
[0124] Step 3: Divide the 20 electrode blocks into two groups of 10 each and weld them into consumable electrodes in a vacuum plasma welding box to obtain 2 consumable electrodes; specifically, the welding current is 460A and the cooling time after welding is 1 hour.
[0125] Step 4, primary melting: The two consumable electrodes obtained in Step 3 are melted in a 3t vacuum consumable arc furnace to obtain two primary ingots. The specifications of the primary ingots after melting are Φ445mm×1500mm.
[0126] Specifically, before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ450mm is selected; melting begins, with the melting current set to 10000A, the melting voltage set to 32V, the melting stirring magnetic field strength set to 21Gs, and the melting speed set to 10kg / min. After heating for 9 minutes, the temperature of the vacuum self-consuming electric arc furnace rises, and bidirectional stirring begins until the self-consuming electrode is completely melted. Then, stirring and heating are stopped, and the furnace is cooled for 6 hours under argon atmosphere.
[0127] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 39°C. The bidirectional stirring operation adopts a method of stirring for 110 seconds, pausing for 35 seconds, and then recirculating. The bidirectional stirring is changed every 30 seconds.
[0128] Step 5: After cooling and exiting the furnace, the two primary ingots are cleaned separately on an ingot cleaning machine. After cleaning, the surfaces of the two primary ingots are black and no metallic color is exposed. Further, the surfaces of the two primary ingots are treated separately. Specifically, the two primary ingots are first shot blasted on a roller conveyor shot blasting machine to remove the black volatiles on the surface. Then, the surface spatter shell is removed on a lathe. Finally, the volatiles are cleaned off on the ingot cleaning machine to expose the metallic color of the primary ingots.
[0129] Step 6, Secondary Melting: The two primary ingots obtained in Step 5 are smelted in a 3t vacuum self-consuming electric arc furnace to obtain one secondary ingot. The secondary ingot after smelting has a size of Φ545mm×2000mm.
[0130] Specifically, before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ540mm is selected; melting begins, with the melting current set to 17000A, the melting voltage set to 34V, the melting stirring magnetic field strength set to 32Gs, and the melting speed set to 17kg / min. After heating for 7 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and bidirectional stirring begins until the primary ingot is melted. Then, stirring and heating are stopped, and the furnace is cooled for 7 hours under argon atmosphere.
[0131] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The bidirectional stirring operation adopts a method of stirring for 70 seconds, pausing for 10 seconds, and then recirculating, with the direction being changed every 8 seconds.
[0132] Step 7: Clean the secondary ingots after cooling and exiting the furnace on an ingot cleaning machine. After cleaning, the surface of the secondary ingots will show a metallic color, and then it will enter the second stage of smelting.
[0133] Step 8, Third Melting: The secondary ingot obtained in Step 7 is melted three times in a 3t vacuum self-consuming electric arc furnace to obtain a total of 1 tertiary ingot. The specifications of the tertiary ingot after melting are Φ645mm×1500mm.
[0134] Specifically, before the three melting processes, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ650mm is selected; melting begins, with the melting current set to 22000A, melting voltage to 36V, melting stirring magnetic field strength to 4Gs, and melting speed to 26kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and bidirectional stirring begins until the secondary ingot is melted. Stirring is then stopped, heating is stopped, and the furnace is cooled under argon atmosphere for 8 hours to obtain the zirconium alloy ingot.
[0135] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The bidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating, and the stirring direction is changed every 10 seconds.
[0136] In this embodiment, the obtained zirconium alloy ingot was sampled and its chemical composition was analyzed. A handheld UT flaw detector was used to conduct ultrasonic flaw detection on the outer circle of the ingot. The test results showed that the zirconium alloy ingot had no defects.
[0137] Comparative Example 2
[0138] This embodiment includes the following steps:
[0139] Step 1: Select nuclear-grade sponge zirconium with a Cl content of 0.08% and prepare the alloying element Nb;
[0140] Step 2: Using a pressing force of 4500t, the weighed nuclear-grade sponge zirconium is pressed into electrode blocks weighing 150kg / block, with the electrode blocks having a size of Φ360mm×300mm.
[0141] Specifically, the screened and tested sponge zirconium was divided into two equal parts by weight. One part of the sponge zirconium was first added into the mold cavity of the press. Then, all the alloying element Nb was evenly sprinkled on the sponge zirconium in the mold cavity. The other part of the sponge zirconium was then added into the mold cavity of the press. Finally, the press was started to press the sponge zirconium, and a total of 20 electrode blocks were obtained.
[0142] Specifically, a 50MN press should be selected;
[0143] Step 3: Divide the 20 electrode blocks into two groups of 10 each and weld them into consumable electrodes in a vacuum plasma welding box to obtain 2 consumable electrodes; specifically, the welding current is 460A and the cooling time after welding is 1 hour.
[0144] Step 4, primary melting: The two consumable electrodes obtained in Step 3 are melted in a 3t vacuum consumable arc furnace to obtain two primary ingots. The specifications of the primary ingots after melting are Φ445mm×1500mm.
[0145] Specifically, before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ450mm is selected, and melting begins. The melting current is set to 12500A, the melting voltage to 34V, the melting stirring magnetic field strength to 25Gs, and the melting speed to 13kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace rises, and unidirectional stirring begins until the self-consuming electrode is completely melted. Then, stirring and heating are stopped, and the furnace is cooled for 6 hours under argon atmosphere.
[0146] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The unidirectional stirring operation adopts a method of stirring for 110 seconds, pausing for 35 seconds, and then recirculating.
[0147] Step 5: After cooling and unloading from the furnace, the two primary castings are surface-cleaned on the ingot cleaning machine. After cleaning, the surfaces of the two primary castings are black and no metallic color is exposed. The first stage of smelting continues.
[0148] Step 6, Secondary Melting: The two primary ingots obtained in Step 5 are smelted in a 3t vacuum self-consuming electric arc furnace to obtain one secondary ingot. The secondary ingot after smelting has a size of Φ545mm×2000mm.
[0149] Specifically, before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ550mm is selected; melting begins, with the melting current set to 19000A, the melting voltage set to 36V, the melting stirring magnetic field strength set to 13Gs, and the melting speed set to 20kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and unidirectional stirring begins until the ingot is completely melted. Then, stirring and heating are stopped, and the furnace is cooled under argon atmosphere for 8 hours.
[0150] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The unidirectional stirring operation adopts a method of stirring for 70 seconds, pausing for 10 seconds, and then recirculating.
[0151] Step 7: After cooling and unloading from the furnace, the secondary ingot is surface-cleaned on an ingot cleaning machine. The surface of the secondary ingot after cleaning is not completely exposed to the metallic color, and it enters the second stage of smelting.
[0152] Step 8, Third Melting: The secondary ingot obtained in Step 7 is melted three times in a 3t vacuum self-consuming electric arc furnace to obtain a total of 1 tertiary ingot. The specifications of the tertiary ingot after melting are Φ645mm×1500mm.
[0153] Specifically, before the three melting processes, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ650mm is selected; melting begins, with the melting current set to 24000A, melting voltage set to 38V, melting stirring magnetic field strength set to 6Gs, and melting speed set to 30kg / min. After heating for 8 minutes, the temperature of the vacuum self-consuming electric arc furnace increases, and bidirectional stirring begins until the secondary ingot is melted. Stirring is then stopped, heating is stopped, and the furnace is cooled under argon atmosphere for 9 hours to obtain the zirconium alloy ingot.
[0154] The crystallizer is equipped with a cooling channel with an inlet water temperature of 35°C and an outlet water temperature of 42°C. The bidirectional stirring operation adopts a method of stirring for 80 seconds, pausing for 20 seconds, and then recirculating, and the stirring direction is changed every 10 seconds.
[0155] In this embodiment, the obtained zirconium alloy ingot was sampled and ultrasonically tested through the outer circle using a handheld UT flaw detector. The results showed that there was a defect reflection wave larger than 2mm at the bottom of the ingot.
[0156] To illustrate the efficacy of this invention, zirconium alloy ingots prepared in Examples 1 to 4 of this invention were further used. These ingots were numbered R90004-1, R90004-2, R90004-3, and R90004-4, respectively. The zirconium alloy ingots prepared in Examples 1 and 2 were numbered R90004-5 and R90004-6. Samples of each ingot were taken for chlorine content analysis using GDMS (glow discharge mass spectrometry). Specific sampling diagrams for each ingot are shown below. Figure 1 As shown in Table 1 below, the chlorine content in each ingot was determined by testing.
[0157] Table 1. Detection results of chlorine content in each ingot.
[0158]
[0159] As shown in Table 1, the chlorine content in the zirconium alloy ingots prepared by this method is significantly lower than that in zirconium alloy ingots prepared by existing processes.
[0160] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention.
[0161] It should be understood that the present invention is not limited to the content already described above, and various modifications and changes can be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a zirconium alloy ingot with low chlorine content, characterized in that, First, the sponge zirconium that has been screened and tested is mixed evenly with alloying elements, and then pressed and welded to obtain a consumable electrode. The consumable electrode is then smelted in the following two stages. During the first stage of smelting, the consumable electrode is placed in the smelting equipment and heating is started. After heating for a set time, unidirectional stirring is started, and intermittent stirring is used to allow the chloride in the consumable electrode to fully volatilize and distribute on the surface of the smelted ingot. After the consumable electrode has melted completely, heating is stopped and cooling is carried out under an inert gas atmosphere. After cooling is completed, the ingot is taken out. The surface of the ingots obtained from the first stage of smelting is cleaned. If the metallic color is exposed, the second smelting stage is started. Otherwise, the surface of the ingots is shot-blasted, turned and cleaned in sequence to remove chlorides, and then the first stage of smelting is carried out. In the second stage of smelting, the ingot with exposed metallic color is first placed into the smelting equipment and heated. After heating for a set time, bidirectional stirring is started, and intermittent stirring is used to ensure that the alloying elements other than chlorine are evenly distributed in the smelted ingot and that chlorides are fully volatilized. After the ingot with exposed metallic color has melted completely, heating is stopped and it is cooled under an inert gas atmosphere. After cooling is completed, a zirconium alloy ingot with a chlorine content of <0.0001% is obtained.
2. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 1, characterized in that, The screened sponge zirconium includes sponge zirconium with a Cl element content of 0.05% to 0.1% and a particle size ≥ 2 mm.
3. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 1, characterized in that, The tested sponge zirconium includes 100% visual inspection, and sponge zirconium with abnormal surface color and no pores is rejected.
4. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 1, characterized in that, The pressing and welding process yields consumable electrodes including: After screening and testing, the sponge zirconium was divided into two parts. One part of the sponge zirconium was added into the press mold cavity. Then, all the alloying elements were evenly sprinkled on the sponge zirconium in the mold cavity. The other part of the sponge zirconium was added into the press mold cavity. Finally, the press was started to press the sponge zirconium to obtain the electrode block. The electrode block is welded in a vacuum plasma welding box, and after cooling for a set time after welding, a consumable electrode is obtained.
5. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 4, characterized in that, When welding in a vacuum plasma welding box, the welding current is set to 400A to 500A; the cooling time is set to 60min to 90min.
6. The method for preparing a low-chlorine content zirconium alloy ingot according to any one of claims 1 to 5, characterized in that, The first stage of melting includes the following process: when the consumable electrode is melted twice in a vacuum consumable arc furnace, the specific process is as follows: Before the first melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ440mm~Φ460mm is selected, and the melting speed corresponding to the crystallizer is 10kg / min~16kg / min; The consumable electrode is first melted, with a melting current of 11000A to 14000A, a melting voltage of 32V to 36V, and a melting stirring magnetic field strength of 23Gs to 27Gs, and unidirectional stirring is used; after the first melting is completed, it is cooled in an inert gas state to obtain a first ingot, and the cooling time is ≥6h. Before secondary melting, the vacuum degree in the vacuum self-consuming electric arc furnace is set to ≤0.5Pa and the pressure rise rate is set to ≤0.3Pa / min; a crystallizer with a diameter of Φ540mm~Φ560mm is selected, and the melting speed corresponding to the crystallizer is 18kg / min~22kg / min; The primary ingot is subjected to secondary melting. During the secondary melting process, the melting current is 17000A~21000A, the melting voltage is 34V~38V, the melting stirring magnetic field strength is 10Gs~16Gs, and unidirectional stirring is adopted. After the secondary melting is completed, it is cooled under an inert gas state to obtain a secondary ingot. The cooling time is ≥7h.
7. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 6, characterized in that, The second stage of smelting includes: smelting the cleaned ingots that have exposed their metallic color on a vacuum arc furnace, setting the vacuum degree in the vacuum arc furnace to ≤0.5Pa and the pressure rise rate to ≤0.3Pa / min before smelting; selecting a crystallizer with a diameter of Φ640mm~Φ660mm, and the smelting speed corresponding to the crystallizer to be 26kg / min~30kg / min; During the smelting process, the smelting current is 22000A~27000A, the smelting voltage is 36V~40V, the smelting stirring magnetic field strength is 4Gs~8Gs, and bidirectional stirring is adopted; after the smelting is completed, it is cooled under an inert gas state to obtain a zirconium alloy ingot with a Cl element content of <0.0001%, and the cooling time is ≥8h.
8. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 7, characterized in that, The bidirectional stirring setting changes the stirring direction every 10 to 20 seconds.
9. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 7, characterized in that, The crystallizers are all equipped with cooling channels, the inlet water temperature of which does not exceed 38°C and the outlet water temperature of which does not exceed 45°C.
10. The method for preparing a low-chlorine-content zirconium alloy ingot according to claim 7, characterized in that, The heating time is 8 to 10 minutes. The intermittent stirring includes unidirectional / bidirectional stirring for 80 to 90 seconds, followed by a 20 to 30 second pause, and then the cycle repeats. The inert gas is argon.
Citation Information
Patent Citations
Method for producing large-sized zirconium ingot with the specification Phi of more than 600mm
CN101597705A
Method for eliminating low-density inclusion defect source of titanium alloy cast ingot
CN113881854A